2020
DOI: 10.21037/tau.2020.03.23
|View full text |Cite
|
Sign up to set email alerts
|

Radical cystectomy: a review of techniques, developments and controversies

Abstract: Radical cystectomy (RC) with urinary diversion is considered the standard treatment for muscle invasive bladder cancer (MIBC). As one of the most challenging surgical techniques performed by urologists, RC was described many decades ago, and yet patient morbidity rates have remained stagnant over the years.This review outlines the most recent indications and techniques for RC and analyses the current landscape of complications after cystectomy. There is significant room for improvement with respect to both onc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 76 publications
0
14
0
Order By: Relevance
“…This latter explanation is supported by a recent multi-centre survey of physicians in 8 countries treating BCG-unresponsive NMIBC patients in which German physicians reported that mitomycin C would be the rst choice of treatment for BCG-unresponsive patients not eligible for cystectomy (12). However, intravesical chemotherapy is considered "oncologically inferior" to radical cystectomy, a procedure known to be associated with considerable peri-operative complications and reduced quality of life (15,16). As such, there is a clear need for novel bladder-preserving treatments for the signi cant number of patients with NMIBC recurrence or progression (17).…”
Section: Discussionmentioning
confidence: 99%
“…This latter explanation is supported by a recent multi-centre survey of physicians in 8 countries treating BCG-unresponsive NMIBC patients in which German physicians reported that mitomycin C would be the rst choice of treatment for BCG-unresponsive patients not eligible for cystectomy (12). However, intravesical chemotherapy is considered "oncologically inferior" to radical cystectomy, a procedure known to be associated with considerable peri-operative complications and reduced quality of life (15,16). As such, there is a clear need for novel bladder-preserving treatments for the signi cant number of patients with NMIBC recurrence or progression (17).…”
Section: Discussionmentioning
confidence: 99%
“…Radical cystectomy (RC) with pelvic lymph node dissection (PLND) is the gold standard treatment for muscle-invasive BCa [ 7 ]. The prognostic and therapeutic value of PLND in patients undergoing RC for urothelial cancer cannot be overstated; however, the optimal extent of dissection remains controversial [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies highlight similar oncological outcomes and lower adverse outcomes, with the potential to improve surgeon precision and dexterity whilst reducing surgeon fatigue, though higher operating costs have restricted its widespread adoption. 8 Because of increasing awareness and concerns about functional implications of standard RC, there is growing interest in organ-sparing cystectomy (OSC) techniques. These techniques aim to maintain similar oncological outcomes to RC but with improvement in sexual and urinary outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to technological advancements, robotic‐assisted RC has grown in popularity in high volume centres. Numerous studies highlight similar oncological outcomes and lower adverse outcomes, with the potential to improve surgeon precision and dexterity whilst reducing surgeon fatigue, though higher operating costs have restricted its widespread adoption 8 …”
Section: Introductionmentioning
confidence: 99%